Distribusi Dana Zakat Terhadap Pelayanan Kesehatan Mustahik Dalam Tinjauan Syariah (Studi Kasus Badan Amil Zakat Nasional Kabupaten Pangkajene Dan Kepulauan) - Hasbiah Hasbiah (Akuntansi, 2023)
Zakat given to mustahik will function as a supporter of their economic growth. The use of zakat funds actually has a careful planning and implementation concept such as studying the triggers of poverty which originate from a lack of money to start a business, lack of a place to work, level of learning, and lack of work ethic, so that with these problems a plan is needed that can increase zakat for capital encouragement. business. With the development of small and medium businesses with capital originating from zakat, it will absorb the workforce and the development of the mustahik's business. This means that the unemployment rate can be reduced, the reduced unemployment rate will result in an increase in people's purchasing power for a product or service, an increase in people's purchasing power will be accompanied by developments in production, this development in the creation zone will be one of the indicators of economic development. and improving the quality of community services.